2016
DOI: 10.1097/mat.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Early Implementation of Video Capsule Enteroscopy in Patients with Left Ventricular Assist Devices and Obscure Gastrointestinal Bleeding

Abstract: Gastrointestinal bleeding (GIB) is a frequent challenge encountered in patients implanted with a left ventricular assist device (LVAD), affecting approximately 25% of this population. Many patients have no identifiable source of bleeding after routine esophagogastroduodenoscopy and colonoscopy and are labeled as obscure GIB (OGIB). Significant costs and invasive procedures are required to investigate and stop the source of bleeding in these patients. We performed a retrospective analysis at a single tertiary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…A large study in non-VAD patients demonstrated the importance of capsule endoscopy guidance for subsequent DBE, with lesions found during the first 60% of the capsule study better suited for upper DBE, and lesions during the last 40% better suited for lower DBE [ 13 ]. Additionally, we found capsule endoscopy to be safe in LVAD patients, with no complications related to VCE, no capsule retention, and no device interference, which is consistent with prior studies [ 12 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…A large study in non-VAD patients demonstrated the importance of capsule endoscopy guidance for subsequent DBE, with lesions found during the first 60% of the capsule study better suited for upper DBE, and lesions during the last 40% better suited for lower DBE [ 13 ]. Additionally, we found capsule endoscopy to be safe in LVAD patients, with no complications related to VCE, no capsule retention, and no device interference, which is consistent with prior studies [ 12 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…[31, 32] The diagnostic yield of capsule endoscopy has been noted to be as low as 20% [14] and as high as 100% in the LVAD population. [33] When capsule endoscopy is abnormal, the most frequent finding is blood in the lumen of the gastrointestinal tract. However, the culprit lesion is directly visualized less than 25% of the time.…”
Section: Resultsmentioning
confidence: 99%
“…However, the culprit lesion is directly visualized less than 25% of the time. [33] This suggests capsule endoscopy can help localize the site of bleeding with VCE but may not visualize the principal bleeding angiodysplasia.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, users of VCE estimated EMI between capsules and cardiac devices possibly being life-threatening for patients. Since the introduction of VCE, several in vitro and in vivo studies analyzed EMI between VCE (PillCam and EndoCapsule) and PMs ( in vitro :[42-44]; in vivo :[44-54]), implantable cardioverter defibrillators (ICD) ( in vitro :[55,56]; in vivo :[45-48,54,56-59]) and left ventricular assist devices (LVAD) ( in vitro : none, in vivo :[52,60-68]).…”
Section: Vce In Patients With Implantable Cardiac Devicesmentioning
confidence: 99%
“…EMI between VCE and LVAD was investigated in 10 in-vivo studies[52,60-68]. No interference was observed in any of the studies.…”
Section: Vce In Patients With Implantable Cardiac Devicesmentioning
confidence: 99%